2012
DOI: 10.1101/gad.193433.112
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the KNOTTED1 regulatory network in maize meristems

Abstract: KNOTTED1 (KN1)-like homeobox (KNOX) transcription factors function in plant meristems, self-renewing structures consisting of stem cells and their immediate daughters. We defined the KN1 cistrome in maize inflorescences and found that KN1 binds to several thousand loci, including 643 genes that are modulated in one or multiple tissues. These KN1 direct targets are strongly enriched for transcription factors (including other homeobox genes) and genes participating in hormonal pathways, most significantly auxin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
318
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(336 citation statements)
references
References 39 publications
17
318
0
1
Order By: Relevance
“…Dominant Lg3 mutants are characterized by leaf patterning defects that include displacement of the ligule over the midrib or deletion of the ligule (Fowler and Freeling, 1996;Muehlbauer et al, 1997Muehlbauer et al, , 1999. lg3 is bound by KN1 and RNAseq data show that lg3 is highly upregulated in Kn1-N leaves (Bolduc et al, 2012b). We found that lg3 transcript is significantly higher in preligule tissue than in blade tissue and is also higher in preligule than in sheath tissue, although this latter difference was not statistically significant ( Figure 4G).…”
Section: Ligule Genes Are Expressed At Multiple Organ Boundariesmentioning
confidence: 58%
See 3 more Smart Citations
“…Dominant Lg3 mutants are characterized by leaf patterning defects that include displacement of the ligule over the midrib or deletion of the ligule (Fowler and Freeling, 1996;Muehlbauer et al, 1997Muehlbauer et al, , 1999. lg3 is bound by KN1 and RNAseq data show that lg3 is highly upregulated in Kn1-N leaves (Bolduc et al, 2012b). We found that lg3 transcript is significantly higher in preligule tissue than in blade tissue and is also higher in preligule than in sheath tissue, although this latter difference was not statistically significant ( Figure 4G).…”
Section: Ligule Genes Are Expressed At Multiple Organ Boundariesmentioning
confidence: 58%
“…Given that KNOX-BEL-auxin modules act in multiple contexts during plant development, it is possible that different SBP family members are expressed depending on context, thus contributing to the elaboration of different developmental boundaries. Intriguingly, two auxin transport genes, Zm-PIN1a and So-PIN1, are upregulated in preligule epidermal cells and are also bound by KN1 and upregulated in Kn1-N mutant leaves (Bolduc et al, 2012b). This finding suggests that KN1 directly activates Zm-PIN1a and SoPIN1 transcription at ectopic boundaries and suggests a model in which auxin transport by PIN proteins is activated at the KNOX presence/absence boundary at the base of wild-type leaf primordia.…”
Section: Ligule Genes Are Expressed At Multiple Organ Boundariesmentioning
confidence: 59%
See 2 more Smart Citations
“…Interactions between cytokinin signaling and homeodomain transcription factors govern meristem maintenance in Arabidopsis, maize, and rice (Gordon et al, 2009;Tsuda et al, 2011;Bolduc et al, 2012). In OsMADS1 knockdown panicles, we detected an overall increased activity of cytokinin pathway genes, examples being LONELY GUY (LOG) family members, a predicted receptor, HKL1/CRL4, and several response regulator (RR) genes (Supplemental Table S4).…”
Section: Osmads1 Negatively Regulates Cytokinin Signaling With Directmentioning
confidence: 83%